Photoelectrochemical Behavior of Simple Synthesized Cl-GQDs/In2O3. Issue 12 (1st December 2022) - Li, Can; Wang, Min; Lei, Yun; Luo, Linhui; Wang, Yongqin; Du, Beibei; Deng, Yifan; Tang, Zehui; Chen, Jiong
Abstract : In this paper, the morphology and photoelectrochemical properties of hydrothermal synthesized chlorine-doped graphene quantum dots (Cl-GQDs) were analyzed by TEM, PL and UV–vis. The Cl-GQDs/In2 O3 were synthesized by an ultrasonic treatment and the morphology, structure and composition, band gap and surface area were analyzed by different techniques. The effect of the mass percentage of Cl-GQDs on the photoelectrochemical (PEC) behavior of In2 O3 was investigated, and the results showed that 3 wt% Cl-GQDs could effectively improve the separation of photogenerated carriers. Moreover, the photocurrent density of 3 wt% Cl-GQDs/In2 O3 was about 10 times as large as that of pure In2 O3 . The cyclic voltammetry (CV) measurements of Cl-GQDs/In2 O3 under dark and light were compared to further investigate the capacitive effect of Cl-GQDs, and the results indicated that Cl-GQDs could store photogenerated electrons, inhibiting the recombination of electron-hole pairs. This work was expected to be helpful for enhancing the PEC performance of In2 O3 and extending the application of Cl-GQDs.